AN ANALYSIS ON THE STUDENTS’ ERROR IN WRITING ARGUMENTATIVE ESSAY OF THE FOURTH SEMESTER STUDENTS IN STKIP PGRI PASURUAN - Rasyidah Nur Aisyah; Firza Rahmawati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2019)
Abstract: For Indonesian learner produce an organized writing in correctly grammar have always been a difficult problem in making written text. It happened since the first language learners have already become the learners’ habit and it influeces the process of using the foreign language. This study investigated common English language errors made by fourth semester students. 34 writing participanted to be the subject of this research and it were obtained from the students’writing task. Errors were involved by collecting samples of learner language, identifying the errors in the sample, describing these errors, classifying them according to their nature and causes, and evaluating their gravity (Keshavarz, 2012). The nine most common errors committed by the participants were, article, tenses, gerund, preposition, word order, agreement, modal, to-infinitivem and active passive. The study is important to educators and study material developers who should become aware of the kind of errors that their target learners make, so they can take into consideration while preparing the teaching material. For learners, error analysis is importantant  as it shows the areas of difficulty in their writing.